Improving agroforestry through effective property rights and collective action - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Agroforestry is a system that combines agriculture and trees. In this system, trees play a prominent role. Different agroforestry systems require different periods of time to develop and manage. Over longer time periods, property rights increase in importance; over larger areas, collective action becomes more important. Depending upon what benefits are sought, farmers will adopt various degrees of joint action or coordination within the landscape.